Respuestas
Respuesta dada por:
0
usando la fórmula resolvente de las cuadráticas:
![\displaystyle{x_{1,2}=\frac{-b±\sqrt{b^2-4ac}}{2a}} \displaystyle{x_{1,2}=\frac{-b±\sqrt{b^2-4ac}}{2a}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%7Bx_%7B1%2C2%7D%3D%5Cfrac%7B-b%C2%B1%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D%7D)
![\mathrm{\large{dónde:}}\begin{cases}a=3\cr b=18\cr c=-50\end{cases} \mathrm{\large{dónde:}}\begin{cases}a=3\cr b=18\cr c=-50\end{cases}](https://tex.z-dn.net/?f=%5Cmathrm%7B%5Clarge%7Bd%C3%B3nde%3A%7D%7D%5Cbegin%7Bcases%7Da%3D3%5Ccr+b%3D18%5Ccr+c%3D-50%5Cend%7Bcases%7D)
![\mathrm{\large{Reemplazando:}} \mathrm{\large{Reemplazando:}}](https://tex.z-dn.net/?f=%5Cmathrm%7B%5Clarge%7BReemplazando%3A%7D%7D)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años